Quantitative foresight modeling to inform the CGIAR research portfolio - Rosegrant, Mark W.; Sulser, Timothy B.; Mason-D'Croz, Daniel; Cenacchi, Nicola; Nin-Pratt, Alejandro; Dunston, Shahnila; Zhu, Tingju; Ringler, Claudia; Wiebe, Keith D.; Robinson, Sherman; Willenbockel, Dirk; Xie, Hua; et al. (International Food Policy Research Institute, 2017)
This report provides a quantitative assessment of the impacts of alternative investment options on the CGIAR’s SLOs (relating to poverty – SLO1, food and nutrition security – SLO2, and natural resources and ecosystem services – SLO3) in the context of changes in population, income, technology, and climate to 2050 as well as for key SDGs of importance to the developing world. The report serves as a source of information and evidence of the impact of CGIAR efforts in agricultural R&D as well as the role of complementary investments. It is intended to help the CGIAR Centers, CG Research Programs (CRP), system management, and donors to complement other efforts to assess the overall impact and benefits of investing in international and national agricultural research programs.